Foliar Sampling Technique in Ber - Ahlawat, V P; Khera, A P; Dahiya, S S (Annals of Arid Zone, 2016)
Different types of leaves wt>re sampled from current season shoot to study the seasonal variation in nutrient content. Mature leaves had the stable plateau of major nutrients from middle of September to middle of November. These leaves may be sampled to find out the nutrient status of her.